Students' Mathematical Literacy Problems during the Online Learning Period - Zulfiyani Labib Abdillah; Hamdan Sugilar; Abdurrahmansyah Abdurrahmansyah; Rizqy Dwi Amrina (Gunung Djati Conference Series, 2022)
During the online learning period, there are obstacles to learning mathematics that affect students' mathematical literacy skills. Therefore, this study aims to find out how to improve mathematical literacy during online learning. The method used in this study is a qualitative research method with a literature review type. The findings reveal that there are many approaches to improve mathematical literacy. However, the researcher only considered several options, namely by increasing the role of the teacher by increasing knowledge related to students' mathematical literacy skills. Then use High Order Thinking learning, because it includes not only numeracy skills but also how to apply mathematics to solve problems in everyday life and how to communicate them. Then, using the Brain-Based Learning learning strategy because there are steps that train curiosity which will stimulate the ability to investigate and interpret mathematical problems in various contexts. As well as using the Blended Learning learning model because it uses internet-based learning to make teaching materials more accessible and accessible at any time. That means, students can communicate with teachers online outside of class hours